Uncovering the wounds in Inxeba-The Wound : the value of posttraumatic public theology for considering masculinity constructions within amaXhosa initiation schools - Fumba, Zukisa Patrick (Stellenbosch : Stellenbosch University, 2023)
Thesis (MTh)--Stellenbosch University, 2023.